Pelaksanaan Sp Tk Pada ODGJ Dengan Gangguan Sensori Persepsi Waham Di Desa Pasar Pedati Kabupaten Bengkulu Tengah - Dinda Dwi Sundari; Inka Putri Adiningsih; Dina Lorenza; Ria Septa Utami; Figo Ageng Andika; Anggraini Saputri Dewi; Ade Herman Surya Direja (Jurnal Dehasen Untuk Negeri, 2024)
Schizophrenia is a mental disorder that causes dysfunction widely. The family as primary care giver plays an important role in helping to meet physical needs, as well as providing psychological support. Apart from dealing with the sufferer's behavior which tends to be unrealistic, the serious challenges felt by schizophrenia caregivers are the imposition of stigma and isolation from the social environment. A delusion is a false belief that is held strongly or continuously, but is not in accordance with reality. The aim is to find out how far the patient is suffering from hallucinations. The method used is a case study with interviews, observations and documentation studies carried out on 02 October 2023 - 06 October 2023 in Pasar Pedati village, Central Bengkulu. After carrying out this activity, the family can find out how to handle the patient when the patient is angry.